2013
DOI: 10.2807/ese.18.15.20447-en
|View full text |Cite
|
Sign up to set email alerts
|

Prevailing effectiveness of the 2009 influenza A(H1N1)pdm09 vaccine during the 2010/11 season in Sweden

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In this study, the vaccine efficacy for A(H1N1)pdm09 strains of 79.6-93.4% was higher than that for the A(H3N2). This is concordant with previous studies, which estimated the vaccine efficacy using serologically based methods and suggested a moderate to high vaccine effectiveness for influenza A(H1N1)pdm09 during the 2010-2014 seasons (Rondy et al, 2015;Widgren et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the vaccine efficacy for A(H1N1)pdm09 strains of 79.6-93.4% was higher than that for the A(H3N2). This is concordant with previous studies, which estimated the vaccine efficacy using serologically based methods and suggested a moderate to high vaccine effectiveness for influenza A(H1N1)pdm09 during the 2010-2014 seasons (Rondy et al, 2015;Widgren et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…The monovalent vaccine licensed in Europe and Canada was adjuvanted, whereas the vaccine licensed in Australia and the United States was not adjuvanted. Subsequent vaccine trials performed with TIV-09 or the adjuvanted forms of MIV-09 demonstrated efficacy (5)(6)(7)(8)(9). In contrast, the nonadjuvanted form of MIV-09 displayed lower effectiveness, low seroprotection in healthy children (35%), and suboptimal response in solid organ transplant recipients and children with systemic lupus erythematosus (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…12 Translated to a wider scale, epidemiological studies have shown decreased rates of ICU admission for H1N1 influenza in countries including Sweden where vaccination is more widely implemented. 14,15 A large multinational study of 5,500 ICU patients showed that ICU patients diagnosed with severe acute respiratory infections were more likely to survive if they had previously been vaccinated against influenza, 16 which has been corroborated. 17 However, whether influenza vaccination is directly responsible for this observed reduction of mortality rates in ICU remains a topic of debate.…”
Section: Influenza Vaccination In Intensive Carementioning
confidence: 89%